1998
DOI: 10.1097/00002030-199818000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in renal function associated with indinavir

Abstract: A crystal nephropathy, characterized by serum creatinine elevation, loss of concentrating ability of the kidney, leukocyturia, and renal parenchymal image abnormalities, is a frequent complication of indinavir therapy. Identification of individuals at risk, particularly those with low body mass index or receiving TMP-SMX prophylaxis, may help the decision to initiate indinavir or chose an alternative protease inhibitor in order to minimize renal and urinary tract adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 10 publications
2
35
1
Order By: Relevance
“…Twice-daily regimens of 800 mg of indinavir plus 100 to 200 mg of ritonavir are considered effective but poorly tolerated, and concerns about the increase in nephrotoxicity have been raised (6). A limited number of patients (n ϭ 7) were affected in our population study, and only a marginal association between C max and this side effect was observed.…”
Section: Discussionmentioning
confidence: 88%
“…Twice-daily regimens of 800 mg of indinavir plus 100 to 200 mg of ritonavir are considered effective but poorly tolerated, and concerns about the increase in nephrotoxicity have been raised (6). A limited number of patients (n ϭ 7) were affected in our population study, and only a marginal association between C max and this side effect was observed.…”
Section: Discussionmentioning
confidence: 88%
“…Prevention of indinavir crystalluria and nephrolithiasis depends on maintenance of a daily fluid intake of at least 1.5 to 2 L. Urinary acidification, although theoretically of benefit, is not generally recommended. Patients who are treated with higher doses (e.g., Ն1000 mg twice daily) over longer periods of time are more likely to develop crystalluria; other risk factors are low lean body mass, co-infection with hepatitis B or C virus, and use of acyclovir or trimethoprim-sulfamethoxazole (84,86,93). In patients who develop indinavir-related nephrolithiasis, therapy usually can be resumed after resolution of the acute episode once adequate volume status is achieved.…”
Section: Renal Toxicity Of Antiretroviral Agentsmentioning
confidence: 99%
“…Reported side effects include lipodystrophy, hyperbilirrubinemia, gastrointestinal malaise, diarrhea and headache. Nephrolithiasis is the most common renal side effect, being reported in 4-9% of individuals [1], but the spectrum of renal and urinary adverse effects of IDV is much larger, as it can be appreciated in the case here presented.…”
mentioning
confidence: 55%